Super-sech Soliton Dynamics in Optical Metamaterials with Generally Parabolic Law of Nonlinearity Using Lagrangian Variational Method - EDAH, GASTON (My University, 2019)
Aims/ Objectives: This paper studies the impact of the generally parabolic law of nonlinearity on the evolution of the energy of super-sech soliton dynamics. Study Design: generally parabolic law of nonlinearity terms study. Place and Duration of Study: Department of Physics, Faculty of Sciences and Technology(FAST), University of Abomey Calavi, Benin. between Febuary 2018 and January 2019. Methodology: Variational approach, namely, the Lagrangian Variational Method (LVM) is presented. The different results are obtained using standard fourth order Runge-Kutta method for integration of the system of ordinary differential equation systems. Results: Dynamics of the different parameters (amplitude, center position, pulse width, chirp, frequency and phase) has been presented with respect to propagating distance. Conclusion: This study reveals that the generally parabolic law of nonlinearity terms don’t affect the energy of the system but influence the pulse phase.
Keywords: Lagrangian approach; generaly parabolic law; super-sech soliton; metamaterial